ECOCIDE DALAM PANDANGAN KRIMINALISASI INTERNASIONAL DENGAN MENGUATNYA IMPUNITAS KORPORASI BERDASARKAN HUKUM PIDANA INTERNASIONAL - Muhammad Reza Syariffudin Zaki; Dion Kasmino Satriano (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract The practice of the emergence of corporate impunity which creates legal uncertainty in terms of environmental crimes in the international sphere, demands more stringent and special arrangements in international agreements. This research is entitled